Indoor winter recreation park and winter sports training center - Agramon, Jahleel Micah P.
Michael Christian Martinez is one of the many athletes who gained fame after qualifying in the Sochi Winter Olympics 2014. Prior to that, most Filipinos probably have not heard about him. This is probably because of lack of government support. Through TV coverage, many Filipinos were able to witness the first Southeast Asian to ever enter the Winter Olympics. According to Mr. Al Marinas, former coach of skating rinks in Megamall and Mall of Asia are used by an average number of 300 leisure skaters per day, along with around 30 skating athletes as stated by Mr. Christopher Martin, the Operation Officer of SM Skating Rink. The increase in the number of skating rink users leads to : less area per skater which means less area needed for training athletes because they have to spin jump turn and glide through different parts of the rink. Moreover, less area may cause collision and injury. Lastly uneven ice surface due to ice scrapes by skating blades, may cause injuries as well. Filipinos have the talent. There is just not enough support and facility. But, providing for both leisure skaters and skating athletes can be very costly. With these, the proponent of the study aims to design a facility that will cater to the needs of the athletes and of the tourists with the strategy of cross-programming sports, recreation and entertainment (to support the expenses of a winter sports facility) as well as utilizing the novelty and excapism that winter sports will provide to the Filipinos to spark interest, support and promotion.